A decolonial mission for critical terrorism studies: interrogating the gendered coloniality and colonial function of the dominant discourse on terrorism - Khan, Rabea M. (Methodologies in critical terrorism studies, 2024)
Increasingly popular calls to “decolonise” have also arrived in the field of Critical Terrorism Studies (CTS). As argued in this chapter, such calls can be problematic and counter-productive to the ethos of the school of decoloniality, especially when it comes to a discipline so closely tied to Terrorism Studies. This chapter reflects on the subtle differences between postcolonial and decolonial approaches and contends that CTS cannot and should not aim to “decolonise” but rather challenge and excavate the gendered-colonial implications, imaginations and logics hidden in the dominant discourse on “terrorism”. As such, a decolonial approach to CTS, it is argued, needs to be aimed at challenging the project of Western (colonial-)modernity, which has produced the racialised and gendered, dominant discourse on “terrorism” today. This discourse perpetuates harmful, racist imaginations of the “terrorist” which are also inherently gendered and ultimately serve the global structures of white supremacy. A theoretical framework investigating the so-called “gendered coloniality” is proposed as one way of studying and uncovering the gendered and racial code inherent to and surrounding the discourse on “terrorism”.